Konsep Deradikalisasi Pada Pendidikan Berbasis Pembelajaran Terpadu - Putri Hergianasari (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2019)
Young people are one of the targets of terrorism groups in recruiting new members. Some terrorists who have been arrested show their status as students or young people. This study discusses the concept of deradicalization in integrated learning-based education, namely on subjects of citizenship, history, religion, also counseling and guidance. In addition, one important way to be developed in the environment of the younger generation is to conduct campaigns against radicalism and peace on a regular basis. This is the right way to improveor recover the situation from radical acts and terrorism. This study uses a literature study method with a qualitative descriptive approach. The unit of analysis of this research is the younger generation who are vulnerable to radicalism. The conclusion is that integrated learning education can strengthen the values ​​of the national character of the younger generation to prevent and fight radicalism.